الكشف الطبوغرافي والهيدرولوجي لبحيرة ساوه وعيونها المائية في العراق باستعمال تقنيات المسح الطبوغرافي ونظم المعلومات الجغرافية - حميد العبدان رحيم (Al-Adab Journal, 2018)
Sawa Lake is one of the most important tourist lakes in Iraq. It is a closed lake located in the southern plateau of Iraq in the arid region. Most of its feeding is groundwater, and there is no clear surface water source feeding it. A topographic survey was conducted for the first time for the rocky cliff, bottom and coasts of lake, Three water springs feeding it were discovered which have distinctive geomorphic characteristics located in the middle of the lake stems from distant depths. High-resolution topographic equipment (2 mm) were used in topographic lift operations. These data have been collected, processed and integrated by using ARC GIs10.2.1. First-time topographic maps of the Lake Bottom, Coast, Rocky Cliff and surrounding areas have been produced based on sea level rise, as well as follow-up of their levels depending on benchmark point. Results of the survey showed topographic differences between the earth’s surface, which ranged between 18.6 - 9m, and the serious decline of water levels were also identified. In this study, which lasted for six years (2012-2017), it was proven that the lake’s level declined from 15.77 m on 17 / 11/2012 to retreat to (13.80 m) on 17/11/2017.